Analysis and application of clutter distribution modeling in UWB SAR difference change detection of target in foliage - Guang-xue WANG; Xiao-tao HUANG; Zhi-min ZHOU (Tongxin xuebao)
In forest area,the intensity backscatter varies quickly.In UWB SAR foliage-concealed target difference change detection,this characteristic had made existing clutter models couldn't fit the clutter distribution accurately.To address the problem,the clutter model suitable for uniform scene was derived.After that,by assuming the intensity of forest area backscatter follows Gamma distribution,the clutter model suitable for serious non-stationary scene was established.And the experimental results showed that,in foliage-concealed target difference change detection,the proposed model could fit the clutter distribution more accurately,and an improved detection performance could be achieved.